2019
DOI: 10.3390/ma12091554
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of ECAP Temperature on the Microstructure and Properties of a Rolled Rare Earth Magnesium Alloy

Abstract: Deformation of an as-rolled rare earth Mg-2Y-0.6Nd-0.6Zr alloy, at different temperatures, was carried out along the BC (90° anticlockwise rotation of the samples after each ECAP pass) route by equal channel angular pressing (ECAP). The effects of the deformation temperature and the predeformation on the microstructure of the magnesium alloy were determined by the microstructure examination. The slip systems and texture change of the Mg-2Y-0.6Nd-0.6Zr alloy were investigated by X-ray diffraction (XRD) and elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Huang et al [76] observed similar fracture mechanisms in a Mg-Al-Ca-Mn alloy exhibiting improved ductility after multi pass ECAP. Akin to the present study, a Mg-2Y-0.6Nd-0.6Zr alloy also exhibited a transition from brittle to ductile fracture with increased dimples and a tearing ridge on ECAP at higher temperatures [77].…”
Section: Fractographysupporting
confidence: 76%
“…Huang et al [76] observed similar fracture mechanisms in a Mg-Al-Ca-Mn alloy exhibiting improved ductility after multi pass ECAP. Akin to the present study, a Mg-2Y-0.6Nd-0.6Zr alloy also exhibited a transition from brittle to ductile fracture with increased dimples and a tearing ridge on ECAP at higher temperatures [77].…”
Section: Fractographysupporting
confidence: 76%
“…The average Schmid factors of the EK30–2.0Ag alloy are slightly higher than those for the EK30 alloy. A higher Schmid factor means that the basal slip is more likely to activate, resulting in a higher elongation of the alloy [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, hightemperature processing leads to precipitation strengthening besides grain refinement and this formation of precipitates may cause inhomogeneous microstructure and grain refinement. Study shows that ECAP processing at high temperatures encourages dynamic recrystallisation resulting in a mixture of elongated and fine grain sizes, and therefore causing non-uniformity in the microstructure [22]. The results on loading and damage on the structure of the specimen, are as shown in Figs.…”
Section: Effect Of Die Temperature On the Processingmentioning
confidence: 86%